Analisis Pendapatan Sopir Angkutan Kota Sebelum Dan Sesudah Pembangunan Terminal Mengwi - Muliawan, Hendra; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
In order to realize a transportation system that is effective and efficient, the government has provided many facilities are expected to be used as well as possible by the public. One is the public transportation which is the best solution for people who want to travel but do not have a personal vehicle. The purpose of this study was to determine the income of city transport driver before and after construction of the terminal Mengwi. In this study also discussed about the factors that affect the income of public transportation drivers. The data used here are the source of the body concerned and reliable. The analysis technique used is regression analysis technique that has been adapted to the subject matter and purpose of the study with the support of data from related parties. In accordance with what has been found that the income tested after construction of public transportation drivers Mengwi terminal decline. Hours of work, transport ownership and driving experience partial have positive effect on earnings city transport driver, while partially rates have negatively affect earnings city transport driver.
Keywords: earnings; hours of work; ownership of transport; tariffs; the driving experience